PENGARUH MOTIVASI BERKUNJUNG TERHADAP MINAT BERKUNJUNG KEMBALI WISATAWAN KE MUSEUM BAHARI JAKARTA - Lyonathan; Dewanta Facrureza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of visiting motivation on tourists' intention to revisit the Jakarta Maritime Museum. The motivation dimension in this study consists of push and pull factors, while the intention to revisit is the desire to revisit and the desire to recommend the museum to others. This study was conducted because the number of visits to the Jakarta Maritime Museum is still low compared to other museums in Indonesia and because of the challenges in increasing the museum's appeal, especially to young people. The research method used was quantitative, with data collection through distributing questionnaires to 100 respondents, visitors to the Jakarta Maritime Museum. The sampling technique used was probability sampling with simple random sampling. Data analysis was performed using IBM SPSS Statistics 26 through validity tests, reliability tests, classical assumption tests, simple linear regression, and coefficient of determination tests. The results showed that all indicators in the motivation and intention to revisit variables were valid and reliable. The simple linear regression analysis showed that motivation had a positive effect on tourists' intention to revisit the Jakarta Maritime Museum, with a regression equation of Y = 5.238 + 0.554X. The regression coefficient of 0.554 indicates that each increase in motivation will increase tourists' intention to revisit. This finding indicates that motivational factors are an important element in encouraging tourists to be interested in repeating visits to the Jakarta Maritime Museum. Keywords: Motivation, Revisit Intention, Tourists, Jakarta Maritime Museum, Tourism.